Biosynthesis of Palladium Nanoparticles Using Shewanella loihica PV-4 for Excellent Catalytic Reduction of Chromium (VI) - Wei Wang; Baogang Zhang; Liu, Qingsong; Du, Penghui; Liu, Wen; He, Zhen (Environ. Sci.: Nano, 2018)
Chromium contamination can be remediated by catalytic reduction with precious metal palladium (Pd). Thus, enhancing Pd catalytic performance is of strong interest. An environmentally friendly and nontoxic approach for production of palladium nanoparticles (Pd-NPs) is to use microorganisms. Herein, the biosynthesis of Pd-NPs by Shewanella loihica PV-4 is reported for the first time. Both extracellular and intracellular bioreduction of Pd(II) has contributed this bio-fabrication, with the production of Pd0 particles in the size range of 4-10 nm. It was found that several factors including a higher initial Pd(II) concentration, weak acid medium condition, and a lager dosage of sodium formate and biomass amount could facilitate this synthesis process. The biosynthesized Pd-NPs exhibited excellent catalytic activities for chromium (VI) reduction, with complete removal of Cr(VI) after 3-h operation with a catalyst amount of 0.5 mg/mL, an initial Cr(VI) concentration of 0.5 mM, and formic acid as electron donor; these are significant advantages to chemically prepared Pd0. Cr(VI) reduction catalyzed by biosynthesized Pd-NPs was promoted with factors such as a higher dosage of formic acid, lower pH, and a lower initial Cr(VI) concentration. Density functional theory calculations of formic acid decomposition on Pd-NPs revealed that Pd-NPs facilitated formic acid to decompose into CO2 and H2. These results have collectively demonstrated the feasibility of the biosynthesis of Pd-NPs by Shewanella loihica PV-4 and its potential application as a promising catalyst for remediation of chromium contamination.